PENERAPAN DEEP LEARNING BERBASIS TEORI KONSTRUKTIVISME DALAM PEMBELAJARAN PENDIDIKAN PANCASILA PADA SISWA KELAS III SEKOLAH DASAR - Aurera Imanuela Inriyanti Nasir Nasir; Eunike Mandolang; Elisabeth Nicolina Sandehang; Novita Sweity Lumantak4; Serra Timbuleng (PT. Giat Konseling Nusantara, 2026)
This study aimed to describe the implementation of deep learning based on constructivist theory in Pancasila Education learning and to analyze its effect on the engagement of third-grade elementary school students. The research employed Classroom Action Research (CAR) with a descriptive qualitative approach and was conducted at SD Negeri 03 Manado involving 24 third-grade students. The research design followed the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection stages. Data were collected through observation, interviews, and documentation and analyzed using the Miles, Huberman, and Saldaña interactive model, including data reduction, data display, and conclusion drawing. The learning process was designed through contextual learning activities, group discussions, reflection sessions, and independent learning tasks that integrated deep learning principles with constructivist theory. The findings revealed that the implementation of deep learning based on constructivism significantly improved student engagement in Pancasila Education learning. Students demonstrated greater participation in discussions, enhanced ability to connect learning materials with real-life experiences, improved reflective thinking, and increased learning independence. The average student engagement increased from 70% before the intervention to 95% after the intervention. These findings indicate that deep learning based on constructivist theory effectively creates meaningful, student-centered, contextual, and reflective learning experiences that enhance student engagement in elementary school Pancasila Education.